Comparing the “value of information services” for providers and vulnerable patrons: a mixed-methods study with academic libraries and students with disabilities - Devendra Potnis; Kevin Mallary (Information Research: An International Electronic Journal)
Introduction. This multi-year, mixed-methods study compares (a) the reasons administrators and librarians of academic libraries invest in assistive technology for delivering information services to students with disabilities, with (b) the benefits that influence these students’ intention to use AT.